Women's discrimination in developing countries : a new data set for better policies - Morrisson, Christian (2005)
Develops two innovative indicators to measure gender inequalities in developing countries. Measures different aspects of constraints imposed on women by social institutions i.e. laws, norms, traditions and modes of conduct that exist in societies for centuries.